1997
DOI: 10.1021/je9601927
|View full text |Cite
|
Sign up to set email alerts
|

Densities, Apparent Molar Volumes, and Apparent Molar Heat Capacities of l-Arginine, l-Proline and d,l-Methionine in Water at 288.15, 298.15, 313.15, and 328.15 K

Abstract: Relative densities, (ρ − ρ°1), and heat capacity ratios, cp ρ/cp °1ρ°1 − 1, for l-arginine, l-proline, and d,l-methionine in water have been measured at 288.15, 298.15, 313.15 and 328.15 K. These data have been used to calculate apparent molar volumes and apparent molar heat capacities. Calculated standard state volumes and heat capacities have been compared to available literature data. Standard state expansibilities have been calculated from the temperature dependences of standard state volume data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 13 publications
(24 reference statements)
3
31
0
Order By: Relevance
“…Thermodynamic studies of (amino acid/peptide + water) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and (amino acid/peptide + salt + water) systems [17][18][19][20][21][22][23][24][25][26][27][28][29] are useful to understand several biochemical processes such as protein hydration, denaturation, aggregation, etc. Nandi and Robinson [30] studied the salting in/salting out effects of several salts on biological macromolecules and inferred that salts interact directly with the peptide group.…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic studies of (amino acid/peptide + water) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and (amino acid/peptide + salt + water) systems [17][18][19][20][21][22][23][24][25][26][27][28][29] are useful to understand several biochemical processes such as protein hydration, denaturation, aggregation, etc. Nandi and Robinson [30] studied the salting in/salting out effects of several salts on biological macromolecules and inferred that salts interact directly with the peptide group.…”
Section: Introductionmentioning
confidence: 99%
“…Values for A v were taken from the compilation by Archer and Wang. (24) The V ∞ m,φ and B v results, together with their standard errors obtained from weighted least-squares analyses of the apparent molar volume data using equation (2), are given in table 3. Table 4 gives a comparison of the V ∞ m,φ and B v results obtained in this study with those reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…HCl appear to be consistent with those of other amino acid systems. (2,13) The apparent molar heat capacities of the amino acid hydrochlorides, C p,m,φ , were obtained from measured relative massic heat capacities using the equation:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations